Corinth in context : comparative studies on religion and society - Friesen, Steven J.; Schowalter, Daniel N., 1957-; Walters, James C. (Novum Testamentum, Supplements, 2010)
This volume is the product of an interdisciplinary conference held at the University of Texas at Austin. Specialists in the study of inscriptions, architecture, sculpture, coins, tombs, pottery, and texts collaborate to produce new portraits of religion and society in the ancient city of Corinth. The studies focus on groups like the early Roman colonists, the Augustales (priests of Augustus), or the Pauline house churches; on specific cults such as those of Asklepios, Demeter, or the Sacred Spring; on media (e.g., coins, or burial inscriptions); or on the monuments and populations of nearby Kenchreai or Isthmia. The result is a deeper understanding of the religious life of Corinth, contextualized within the socially stratified cultures of the Hellenistic and Roman periods.